2015
DOI: 10.3389/fpsyg.2015.00384
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-active gap filling

Abstract: Much work has demonstrated that speakers of verb-final languages are able to construct rich syntactic representations in advance of verb information. This may reflect general architectural properties of the language processor, or it may only reflect a language-specific adaptation to the demands of verb-finality. The present study addresses this issue by examining whether speakers of a verb-medial language (English) wait to consult verb transitivity information before constructing filler-gap dependencies, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 101 publications
10
61
1
1
Order By: Relevance
“…Boston, Hale, Patil, Kliegl, & Vasishth, 2008;Dikker, Rabagliati, & Pylkkänen, 2009;Hale, 2001;Lau, Stroud, Plesch, & Phillips, 2006;Levy, 2008;Smith & Levy, 2013;Staub & Clifton, 2006) and other syntactic properties (e.g. Ilkin & Sturt, 2011;Omaki et al, 2015) of upcoming words. In our experiments, the target word is always preceded by a syntactically constraining context, and so participants should be able to quickly anticipate that the next word is likely to be a verb across all conditions.…”
Section: Syntactic Parsing Is Slowmentioning
confidence: 98%
“…Boston, Hale, Patil, Kliegl, & Vasishth, 2008;Dikker, Rabagliati, & Pylkkänen, 2009;Hale, 2001;Lau, Stroud, Plesch, & Phillips, 2006;Levy, 2008;Smith & Levy, 2013;Staub & Clifton, 2006) and other syntactic properties (e.g. Ilkin & Sturt, 2011;Omaki et al, 2015) of upcoming words. In our experiments, the target word is always preceded by a syntactically constraining context, and so participants should be able to quickly anticipate that the next word is likely to be a verb across all conditions.…”
Section: Syntactic Parsing Is Slowmentioning
confidence: 98%
“…A critical test for such hypotheses is the relative timing of activation across the course of a sentence. In particular, a substantial body of research has found that syntactic processing can be highly predictive (Levy & Keller, ; Omaki et al, ; Staub & Clifton, ; Sturt & Lombardo, ). If the IFG and the PTL are involved in lexical–syntactic processing, they might show early effects of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using different experimental techniques has demonstrated that comprehenders can use various sources of information to compute thematic relations predictively (Altmann & Kamide, 1999;Aoshima, Phillips, & Weinberg, 2004;Ferretti, McRae, & Hatherell, 2001;Kamide, Altmann, & Haywood, 2003;Knoeferle, Crocker, Scheepers, & Pickering, 2005;McRae, Hare, Elman, & Ferretti, 2005;Omaki et al, 2015). For example, McRae et al (2005) reported that participants were faster to name a verb when it was preceded by a noun that was a typical event participant (e.g., agent, patient) and suggested that comprehenders can use nouns to pre-activate the classes of events in which they typically play a role (see also Hare, Jones, Thomson, Kelly, & McRae, 2009).…”
Section: Prediction In the Processing Of Thematic Relationsmentioning
confidence: 99%
“…For example, listeners are more likely to direct their eye-gaze to a picture of an edible object (e.g., a cake) when they hear the beginning of an utterance like 'The boy will eat…' compared to a neutral utterance such as 'The boy will move…' (Altmann & Kamide, 1999). Further, much evidence has suggested that comprehenders compute rich expectations about upcoming inputs at multiple levels of representation (syntactic: Ilkin & Sturt, 2011;Lau, Stroud, Plesch, & Phillips, 2006;Levy, Fedorenko, Breen, & Gibson, 2012;Omaki et al, 2015;Staub & Clifton, 2006;Wicha et al, 2004;Van Berkum et al, 2005;Yoshida, Dickey, & Sturt, 2013;lexico-semantic: Federmeier & Kutas, 1999;Kutas & Hillyard, 1984;Otten & Van Berkum, 2008;Szewczyk & Schriefers, 2013; phonological and orthographic: Delong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkanen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Farmer, Yan, Bicknell, & Tanenhaus, 2015;Kim & Lai, 2012;Laszlo & Federmeier, 2009). Here, we operationally define 'prediction' as the pre-activation of stored representations before the bottom-up input is encountered, and we will make no a priori assumptions regarding the nature of the mechanisms involved (e.g., whether they are automatic or controlled).…”
Section: Prediction In Language Comprehensionmentioning
confidence: 99%